Montane Foragers : Asana and the south-central Andean archaic - Aldenderfer, Mark S. (University of Iowa Press, 1998)
"All previous books dealing with prehistoric hunter-gatherers in the high Andes have treated ancient mountain populations from a troglodyte's perspective, as if they were little different from lowlanders who happened to occupy jagged terrain. In Montane Foragers, Mark Aldenderfer builds a unique and penetrating model of montane foraging that justly shatters this traditional approach to ancient mountain populations." "Aldenderfer's investigation elucidates elevational stress - what it takes for humans to adjust and survive at high altitudes. In a masterful integration of mountain biology and ecology, he emphasizes the nature of hunter-gatherer adaptations to high-mountain environments." "Aldenderfer's detailed archaeological case study of high-elevation foraging adaptation, his description of this extreme environment as a viable human habitat, and his theoretical model of montane foraging create a new understanding of the lifeways of foraging peoples worldwide."--Jacket